Analisis Fractography dan Kegagalan Fuel Injection Valve Diesel Power Plant PT.XYZ Area Bali - ANDI IRIYANTO (Energi & Kelistrikan, 2021)
To meet the electricity needs in tiga nusa, so far it has been served with an isolated grid system with Diesel Generators. To improve the reliability of Diesel Engines from Fuel Injection Valve interference is to test Fuel-Injection Valve whether or not meets the relevant specifications at certain condition to prevent repeated failures. On December 10, 2019 (Running Hours 15,505), there was a disturbance with an indication of a decrease in the temperature of the unit 1 cylinder, After inspection, it was found that there was no atomizing and the Fuel Injection Valve was cracked. The preparation of this report is carried out to find the root of the problem so that it can determine the right Failure Defense Task (FDT) to prevent the disturbance from reoccurring.